2022
DOI: 10.1177/0143831x221099663
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional configuration of platform work: A mixed-methods analysis of the Argentinian case

Abstract: The aim of this article is to make a contribution to understanding platform work in a comprehensive and geographically situated way, and thus to consider comprehensive responses to its precarising character. The author proposes an analytical framework in which platform work is the result of the articulation of three dimensions: technological-organisational, institutional and ideological. In turn, this framework is applied in depth to a case study: delivery platform work in Argentina. To that end a mixed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Thirdly, the remuneration system used by each type of platform leads to different types of resistance. Delivery workers, who are paid a fixed rate set by the platform, have limited possibilities to manage their own working time and reduce unpaid times through individual strategies, so that collective action in terms of claiming better fees and also being able to charge waiting times has become relevant (Haidar, 2022). In contrast, designers building a robust reputation and getting numerous clients enhance their work price by including certain unpaid time.…”
Section: Discussion and Main Conclusionmentioning
confidence: 99%
“…Thirdly, the remuneration system used by each type of platform leads to different types of resistance. Delivery workers, who are paid a fixed rate set by the platform, have limited possibilities to manage their own working time and reduce unpaid times through individual strategies, so that collective action in terms of claiming better fees and also being able to charge waiting times has become relevant (Haidar, 2022). In contrast, designers building a robust reputation and getting numerous clients enhance their work price by including certain unpaid time.…”
Section: Discussion and Main Conclusionmentioning
confidence: 99%
“…The field of industrial relations labour covers various studies exploring multifaceted aspects of platform work. Research topics include the influence of gig companies on workers' market risk exposure (Maffie 2023), investigation of microwork geography and the classification of worker types (Morgan, van Zoonen and ter Hoeven 2023), platform classification systems (Maffie 2020), multidimensional configuration of platform work (Haidar 2022), and the role of algorithmic management in platform work (Duggan et al 2019;Kullmann 2018). These papers contribute to a comprehensive understanding of the challenges and opportunities in the evolving industrial relations landscape of OLPs.…”
Section: And Authorsmentioning
confidence: 99%
“…Finally, various studies have reported, but have not elaborated on, socio‐ideological forms of control aimed at influencing platform workers' values, beliefs, and identities, ‘shaping subjects and social relations, so that they plug into the processes of capital accumulation’ (Gregory & Sadowski, 2021; p.4). The literature variously refers to these forms of control as: techno‐normative control (Gandini, 2018), fictitious freedom (Shibata, 2019), nontraditional normative control (Veen et al, 2019), normative mechanisms (games and symbolic rewards) (Vallas & Schor, 2020), soft forms of control (Rosenblat, 2018), ideal of entrepreneurial self (Haidar, 2022), self‐entrepreneurship with an ideal of hyper‐meritocratic justice (Galière, 2020), biopolitical platforms and the perverse virtues (Gregory & Sadowski, 2021), and narratives of platform work as a leisure or economic opportunity (Stewart et al, 2020). It has thus been recognised that platform companies encourage workers to see themselves as entrepreneurs or autonomous workers, thereby legitimising their status as independent contractors and boosting their subjective adherence to the work regime these companies offer (Gandini, 2018; Rosenblat, 2018; Shapiro, 2017; Shibata, 2019; Vallas & Schor, 2020).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Managerial control strategies used by platform companies have been the subject of empirical research and theoretical discussion regarding the particularities of a triangular business model based on a digital infrastructure (e.g., online platforms operating through a website or app) and with an open employment relationship (Gandini, 2018; Kaine & Josserand, 2019; Shapiro, 2020; Vallas & Schor, 2020). One of the most relevant findings of this literature is that a key element of the platform business model is the concentration of great organisational power over the work process while simultaneously allowing workers a certain degree of autonomy and encouraging them to see themselves as self‐employed (Gregory & Sadowsi, 2021; Haidar, 2022; Shapiro, 2017; Vallas & Schor, 2020).…”
Section: Introductionmentioning
confidence: 99%